Genome-wide average DNA methylation is determined in utero. (6th March 2018) - Li, Shuai; Wong, Ee Ming; Dugué, Pierre-Antoine; McRae, Allan F; Kim, Eunae; Joo, Ji-Hoon Eric; Nguyen, Tuong L; Stone, Jennifer; Dite, Gillian S; Armstrong, Nicola J; Mather, Karen A; Thalamuthu, Anbupalam; et al.
Abstract: Background: Investigating the genetic and environmental causes of variation in genome-wide average DNA methylation (GWAM), a global methylation measure from the HumanMethylation450 array, might give a better understanding of genetic and environmental influences on methylation. Methods: We measured GWAM for 2299 individuals aged 0 to 90 years from seven twin and/or family studies. We estimated familial correlations, modelled correlations with cohabitation history and fitted variance components models for GWAM. Results: The correlation in GWAM for twin pairs was ∼0.8 at birth, decreased with age during adolescence and was constant at ∼0.4 throughout adulthood, with no evidence that twin pair correlations differed by zygosity. Non-twin first-degree relatives were correlated, from 0.17 [95% confidence interval (CI): 0.05–0.30] to 0.28 (95% CI: 0.08–0.48), except for middle-aged siblings (0.01, 95% CI: −0.10–0.12), and the correlation increased with time living together and decreased with time living apart. Spouse pairs were correlated in all studies, from 0.23 (95% CI: 0.3–0.43) to 0.31 (95% CI: 0.05–0.52), and the correlation increased with time living together. The variance explained by environmental factors shared by twins alone was 90% (95% CI: 74–95%) at birth, decreased in early life and plateaued at 28% (95% CI: 17–39%) in middle age and beyond. There was a cohabitation-related environmental component of variance. Conclusions: GWAM is determined in utero by prenatal environmental factors, the effects of which persist throughout life. The variation of GWAM is also influenced by environmental factors shared by family members, as well as by individual-specific environmental factors.